IL‐10 producing type 2 innate lymphoid cells prolong islet allograft survival. Issue 11 (9th October 2020) - Huang, Qingsong; Ma, Xiaoqian; Wang, Yiping; Niu, Zhiguo; Wang, Ruifeng; Yang, Fuyan; Wu, Menglin; Liang, Guining; Rong, Pengfei; Wang, Hui; Harris, David CH; Wang, Wei; et al.
Abstract: Type 2 innate lymphoid cells (ILC2s) are a subset of ILCs with critical roles in immunoregulation. However, the possible role of ILC2s as immunotherapy against allograft rejection remains unclear. Here, we show that IL‐33 significantly prolonged islet allograft survival. IL‐33‐treated mice had elevated numbers of ILC2s and regulatory T cells (Tregs). Depletion of Tregs partially abolished the protective effect of IL‐33 on allograft survival, and additional ILC2 depletion in Treg‐depleted DEREG mice completely abolished the protective effects of IL‐33, indicating that ILC2s play critical roles in IL‐33‐mediated islet graft protection. Two subsets of ILC2s were identified in islet allografts of IL‐33‐treated mice: IL‐10 producing ILC2s (ILC2 10 ) and non‐IL‐10 producing ILC2s (non‐ILC 10 ). Intravenous transfer of ILC2 10 cells, but not non‐ILC 10, prolonged islet allograft survival in an IL‐10‐dependent manner. Locally transferred ILC2 10 cells led to long‐term islet graft survival, suggesting that ILC2 10 cells are required within the allograft for maximal suppressive effect and graft protection. This study has uncovered a major protective role of ILC2 10 in islet transplantation which could be potentiated as a therapeutic strategy. Synopsis: This study reveals a major protective role of the IL‐33/ILC2 axis in islet transplantation that could be potentiated as a therapeutic strategy. Adoptive transfer of ex vivo expanded IL‐10‐producing ILC2s (ILC210) significantly prolonged allograft survival. IL‐33 significantly prolonged islet allograft survival by increasing numbers of ILC2s and regulatory T cells in vivo . IL‐33 treatment induced a long‐term accumulation of ILC2s in islet graft associated with a persistent increase of IL‐33 in islet graft tissue. Expansion of ILC210 was induced by IL‐33 and IL‐2/IL‐2 antibody complex in vivo and in vitro . ILC210 prolonged islet allograft survival in an IL‐10-dependent manner. ILC210 migration into the islet allograft was necessary for maximum graft protection. The phenotypic stability of locally transferred ILC210 was an important factor in determining the fate of islet grafts. Abstract : This study reveals a major protective role of the IL‐33/ILC2 axis in islet transplantation that could be potentiated as a therapeutic strategy. Adoptive transfer of ex vivo expanded IL‐10‐producing ILC2s (ILC210) significantly prolonged allograft survival.